The assesment of inclusiveness principle of Malaysian new economic model: Maqashid Syar’iyyah perspective - Rahman, Riki; Haron, M. Sabri; Possumah, Bayu T. (Journal Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2015)
The Assesment of Inclusiveness Principle of Malaysian New Economic Model: Maqashid Syar’iyyah Perspective. Objective of this article is to assess how far the principles of inclusiveness in the Economic New Model in Malaysia can fulfil the needs of maqasid syar’iyyah. The assessment is conducted through the key concepts and strategic measures of the principles of inclusiveness. This study is a qualitative which descriptive and analytical approach is used for assessing the principles of inclusiveness in the Economic New Model based on maqasid syar’iyyah perspective. The method of this study is using the literature review with references from secondary data. This study is expected to provide recommendations about the important role of maqasid syar’iyyah for maintaining the welfare of society and developing of a country, in this context for developing the Malaysian economy, in line with the vision 2020, Malaysia on par with developed countries.